Canna indica L and Spirulina platensis for Food Security - Nita Noriko; Risa Swandari Wijihastuti; Alina Primasari; Analekta Tiara Perdana; Hidayat Yorianta Sasaerila (Postgraduate, University of Mataram, 2023)
Climate change threats to food security, because it decreases agricultural productivity. C. indica L can adapt to environment and produce white and red rhizomes. Dominant content both of rhizomes are carbohydrates which increase protein as nutrition by adding S platensis. The research aims to determine potential of composite flour of C. indica L and S. platensis as alternative healthy foodstuff for food security. The method consists of formulation composite flour, proximate tests, determining amino and fatty acids, in vitro growth tests of Lactobacillus, cookies and meatball formulations. The result showed composite flour from red rhizome (RRCS) contains 11% water, 21.745% protein, 0.5% lipid, 9.99% dietary fiber, 57.81% carbohydrates, and 8.94% ash.Â While white rhizome (WRCS) contains, 8.75% water, 17.41 protein, 0.29% lipid, 9.54% dietary fiber, 67.601% carbohydrates and 5.94% ash. Amino and fatty acid appears in both composite flours were similar, except proline and oleic acid higher in RRCS.Â Lignoceric founded only in WRCS. In vitro test showed Lactobacillus (BAL) grew on modified MRSA from RRCS and WRCS. Both of composite flour processed into marketable cookies and meatballs formulations. Based on the result, C. indica L and S. platensis composite flour can be used as alternative food for food security.